Evaluation of DNA vaccines against Mycoplasma nasistruthionis sp. nov. str. Ms03 infections in ostriches and the production of IgA heavy chain proteins - Jonker, Hester Isabella (2017)
Thesis (MSc)--Stellenbosch University, 2017.